Development of the Trust Issue in the Movie Raya and the Last Dragon - Sri Wulan Wulan (ITScience (Information Technology and Science), 2021)
The study discusses the development of Raya’s trust issue in the movie. The qualitative method is applied to analyze the data in this study. The result shows that the protagonist in the film suffers from trust issues. There are two reasons to trigger her trust issue. T. Her friend betrays her. Her friend and her people try to steal her village’s gem. This hurt the protagonist. This protagonist makes her start hard to trust anyone else. Next is trauma. Losing her village, Kumandra leaves her traumatic. She begins to show signs of trust issues. Some signs of her trust issue are overprotective toward Sisu, her beloved dragon, being wary, and keeping distance from others. The protagonist expresses such characters. She fears something terrible which can happen to Sisu. Therefore, she never trusts other people around her. She also distances herself from other people because of wariness. Sisu sees this. Sisu thinks that such a trust issue will make Raya in trouble. Finally, Sisu tries hard to teach Raya to trust other people. They eventually succeed in building Raya’s trust in others, and then a magical work happens as the impact of her trust.